Xilinx software controlled single phase PWM inverter / Mohammad Ezanni Mat Salleh - Mat Salleh, Mohammad Ezanni (2017)
This report involves constructing a full bridge inverter circuit that is suitable for Uninterruptible Power Supplies (UPS), using the Insulated Gate Bipolar Transistors (IGBT) as the main switching devices. The Xilinx Complex Programmable Logic Devices (CLPD) is used to generate the control signal for required Pulse Width Modulation (PWM) switching pattern. The PWM switching techniques enable the output voltage to be controlled by changing the Modulation Index (Ma). Two types of PWM switching techniques: Sinusoidal and Straight-line PWM are considered.